2012
DOI: 10.1590/s0044-59672012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Time-variations of equivalent water heights'from Grace Mission and in-situ river stages in the Amazon basin

Abstract: Gravity Recovery and Climate Experiment (GRACE) mission is dedicated to measuring temporal variations of the Earth's gravity field. In this study, the Stokes coefficients made available by Groupe de Recherche en Géodésie Spatiale (GRGS) at a 10-day interval were converted into equivalent water height (EWH) for a ~4-year period in the Amazon basin (from July-2002 to May-2006). The seasonal amplitudes of EWH signal are the largest on the surface of Earth and reach ~ 1250mm at that basin's center. Error budget re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…The same behavior of slope coefficient of the regression line a observed by ALMEIDA et al (2011) was found in this study. Generally decreases from up to down stream in most of major rivers of Amazon basin.…”
Section: Comparison Between Grace Ewh and In-situ (Ana) Time Seriessupporting
confidence: 90%
“…The same behavior of slope coefficient of the regression line a observed by ALMEIDA et al (2011) was found in this study. Generally decreases from up to down stream in most of major rivers of Amazon basin.…”
Section: Comparison Between Grace Ewh and In-situ (Ana) Time Seriessupporting
confidence: 90%
“…These results are consistent with those reported by Almeida et al . [] and Frappart et al . [] for the Amazon region.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that GRACE data may represent the TWS change in the Brazilian Cerrado satisfactorily; allowing assessment of the seasonality of the water balance in this region. These results are consistent with those reported by Almeida et al (2012) and Frappart et al (2013) for the Amazon region. The El Niño events of 2007 and 2010 are probably responsible for the major droughts in the watersheds studied.…”
Section: Water Budget and Trends In The Cerradosupporting
confidence: 93%